Motivasi Belajar Lansia Pada Program Keaksaraan Di Kampung Bungaraya Kecamatan Bungaraya Kabupaten Siak - Ajeng Atikah Merlinda; Syafrizal Syafrizal (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This research was conducted in Bungaraya Village, Bungaraya District, Siak Regency, Riau Province. The aim was to determine the learning motivation of elderly people in the literacy program in Bungaraya Village, and to determine the results of the literacy education program in Bungaraya Village. This research method uses descriptive qualitative research methods and data collection using in-depth interview techniques, direct observation and documentation. With a total of seven subjects coming from the community, with the condition that subjects other than village people include transmigrants who have lived in the village for decades, and are deemed capable of defining and explaining a problem solving process based on existing facts. The theories used are social action theory and motivation theory. Field research found that the learning motivation of elderly people in literacy programs is quite high and the results of literacy programs are very effective in eradicating cases of illiteracy. The government, administrators and tutors work together to continue efforts to eradicate illiteracy. The literacy program is an effective step for the government to always pay attention to its people in social, development and educational matters.